The responses to long-term nitrogen addition of soil bacterial, fungal, and archaeal communities in a desert ecosystem - Zhang, Xuan; Song, Xin; Wang, Taotao; Huang, Lei; Ma, Haiyang; Wang, Mao; Tan, Dunyan (Frontiers in Microbiology, 2022)
Nitrogen (N) deposition is a worldwide issue caused by human activity. Long-term deposition strongly influences plant productivity and community composition. However, it is still unclear how the microbial community responds to long-term N addition in a desert ecosystem. Therefore, a long-term experiment was conducted in the Gurbantonggut Desert in northwestern China in 2015. Four N addition rates, 0(CK), 5(N1), 20(N2), and 80(N3) kg N ha-1 yr-1, were tested and the soil was sampled after 6 years of N addition. High-throughput sequencing (HTS) was used to analyze the soil microbial composition. The HTS results showed that N addition had no significant effect on the bacterial α- and β-diversity (p > 0.05) but significantly reduced the archaeal β-diversity (p < 0.05). The fungal Chao1 and ACE indexes in the N2 treatment increased by 24.10% and 26.07%, respectively. In addition, N addition affected the bacterial and fungal community structures. For example, compared to CK, the relative abundance of Actinobacteria increased by 17.80%, and the relative abundance of Bacteroidetes was reduced by 44.46% under N3 treatment. Additionally, N addition also changed the bacterial and fungal community functions. The N3 treatment showed increased relative abundance of nitrate-reducing bacteria (27.06% higher than CK). The relative abundance of symbiotrophic fungi was increased in the N1 treatment (253.11% higher than CK). SOC and NH4+-N could explain 62% of the changes in the fungal community function. N addition can directly affect the bacterial community function or indirectly through NO3–N. These results suggest that different microbial may have various responses to N addition. Compared with bacteria and fungi, the effect of N addition had less effect on the archaeal community. Meanwhile, N-mediated changes of the soil properties play an essential role in changes in the microbial community. The results in the present study provided a reliable basis for an understanding of how the microbial community in a desert ecosystem adapts to long-term N deposition.